Rewrite x2 − 6x + 7 = 0 in the form (x − a)2 = b, where a and b are integers, to determine the a and b values.

a = 4 and b = 3
a = 3 and b = 2
a = 2 and b = 1
a = 1 and b = 4

Respuesta :

Answer:

a = 3 and b = 2

Step-by-step explanation:

From completion of squares:

[tex] {x}^{2} - 6x + 7 = 0 \\ \{ {x}^{2} - 6x + { (\frac{6}{2} )}^{2} \} + 7 - {( \frac{6}{2}) }^{2} = 0 \\ ( {x}^{2} - 6x + {3}^{2} ) = 2 \\ { \boxed {{(x - 3)}^{2} = 2}}[/tex]

a is 3

b is 2

Answer:

Answer B : a = 3 and b = 2

Step-by-step explanation:

Give man above brainlyiest he deserives it